IMPLEMENTASI KURIKULUM MERDEKA BERBASIS LITERASI PADA SEKOLAH PENGGERAK DI SD GMIT AIRNONA 1 KOTA KUPANG - Yesli Ivana Seran; Hendrik A.E Lao; Umar Ali (Jurnal Dedikasi Pendidikan, 2023)
The literacy-based independent curriculum is the government's attempt to return the education system to the essence of the law by giving schools, teachers and students the freedom to innovate. In addition, literacy is also the main focus in the development of the Independent Curriculum, of course, in addition to numeracy skills. Literacy skills refer to the abilities and skills of a person in reading, writing, calculating and solving problems with certain skills needed in everyday life. The purpose of this research is to find out whether the driving school at SD GMIT Airnona 1 Kupang has implemented a literacy-based independent curriculum. And knowing the obstacles that hinder SD GMIT Airnona 1 Kupang as a driving school in implementing a literacy-based independent curriculum. The research location was determined deliberately. The research method used is qualitative with a phenomenological approach. Sources of data were taken from the school principal and two driving teachers, this study used data triangulation techniques, data collection techniques in the form of observation, interviews and documentation. The results showed that the implementation of a literacy-based independent curriculum at GMIT Airnona 1 Elementary School, Kupang City: 1. It has been implemented because this school is the first generation driving school in Kupang City. It can be seen from the two driving teachers who use the independent teaching platform application to make it easier for teachers to carry out learning and teaching and learning activities. Teachers are seen preparing learning implementation plans, learning methods according to student needs, media that attract students, and applying differentiation learning, in which the teacher responds to or responds to student learning needs as seen from the application of literacy from grade 1 to grade 5 at SD GMIT Airnona 1 Kota Kupang . 2. The obstacles faced by schools in implementing the literacy-based independent curriculum are that teachers are not proficient in mastering ICT, inadequate infrastructure, mastery of the independent curriculum there is no willingness from the teacher to change in a better direction.